The Brazilian new middle class stratagem: dialectics of consumption and overexploitation of labour renewal - Abdala, Paulo Ricardo Zilio; Misoczky, Maria Ceci Araújo (Organizações & Sociedade, 2019)
The argument of this essay is that the ideia of emergence of a new Brazilian middle class was a stratagem adopted to create a positive agenda with transitory social consensus. In order to develop it, we return to the social class theory to discuss the stratification theory, methodological and theoretical support of the so called new middle class. In addition to that, another possibility of analysis is presented, based on the theoretical propositions by Alvaro Vieira Pinto and Ruy Mauro Marini, two authors from the Brazilian social thought, articulating consumption, social classes, work and production as inseparable relations, part of dependent capitalism contradictions. From these authors perspective, it was possible to understand that the expansion of consumption, basis for the new middle class stratagem, temporarily improved the living conditions of people at the expense of deepening the overexploitation of labor, reproducing the development of dependency.